Surgical Treatment of Segond Fractures in Acute Anterior Cruciate Ligament Reconstruction. Issue 10 (28th September 2017) - Ferretti, Andrea; Monaco, Edoardo; Wolf, Megan Rianne; Guzzini, Matteo; Carli, Angelo De; Mazza, Daniele
Background: The Segond fracture is an avulsion-type fracture located on the anterolateral aspect of the tibia associated with a ligament recently termed the anterolateral ligament . This injury has been described as pathognomonic for an anterior cruciate ligament (ACL) tear and is associated with a higher grade pivot shift. Purpose: To present and report 2-year clinical outcomes of a surgical technique for acute ACL reconstruction with fixation of a concomitant Segond fracture. Study Design: Case series; Level of evidence, 4. Methods: A retrospective chart review was performed of patients who underwent acute reconstruction for a complete ACL tear with concomitant Segond fracture fixation between January 2010 and December 2014; surgery was performed by a single surgeon. Patients underwent direct Segond fracture repair by either suture alone, suture anchor, or cannulated screw fixation based on the size of the lesion, followed by a 2-incision hamstring autograft intra-articular reconstruction. Pre- and postoperative KT-1000 arthrometer assessment, Lachman test, and pivot-shift test were performed, and patients were administered validated subjective outcome surveys. Results: Twelve patients met inclusion criteria for this review. The measured pre- and postoperative objective and subjective scores were significantly improved in all patients. Side-to-side anterior laxity was significantly improved in all patients based on Lachman and KT-1000 arthrometer testing. A significant pivot shift demonstrated preoperatively (3+, n = 11 [92%]; 2+, n = 1 [8%]) was corrected after fixation, except in 1 patient (8%), who maintained a 1+ pivot shift. Lysholm, Tegner, and International Knee Documentation Committee subjective and objective scores were significantly improved. At a minimum 2-year follow-up, no patients reported rerupture, and only 1 patient (8%) underwent a subsequent procedure (a meniscectomy). No major or minor complications were reported, and all patients returned to their previous activity levels at a mean of 6 months postoperatively. Conclusion: Direct repair of the Segond fracture and plication of the anterolateral capsule in patients with an ACL rupture and a high-grade pivot shift demonstrate good clinical outcomes, restoration of rotational stability, and maintenance of knee range of motion at 2 years postoperatively, with no major complications.